Life and work of Oscar Valdivia Ponce, one hundred years after his birth - Huarcaya-Victoria, Jeff (2020)
Recently it was celebrated one hundred years of the birth of Oscar Valdivia Ponce (1919-2001), a psychiatrist and “Sanmarquino” by training. This article aims to realize an approach to his life and work, considering his engagement in the historical, social and cultural scientific research. The main contribution of Valdivia was getting to learn and understand the Peruvian men and his relationship to culture. He also wrote about the history of Peruvian Psychiatry, rooted on a cultural and social doctrine. It behooves our generation to reconceptualize what Valdivia researched according to the body of knowledge that we have. Each generation of physicians, in general, and psychiatrists, in particular, has to rethink what they are doing, as Valdivia would have wanted.